2010
DOI: 10.1037/a0019316
|View full text |Cite
|
Sign up to set email alerts
|

“Everyone knows their Miranda rights”: Implicit assumptions and countervailing evidence.

Abstract: In its landmark decision in Miranda v. Arizona (1966), the Supreme Court of the United States buttressed the Constitutional privilege against self-incrimination by requiring as a procedural safeguard that various aspects of this privilege be clearly communicated to custodial suspects. Members of the public often believe that their continually media-fueled familiarity with Miranda warnings results in an adequate understanding of Miranda rights-a frequently erroneous assumption that may diminish counsel's motiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 13 publications
1
67
0
2
Order By: Relevance
“…On average, they evidenced only 2.11 (SD = .90) Miranda misconceptions. Comparatively, this percentage of high performers is slightly higher than found with college undergraduates in general (i.e., 48.7%; see Rogers et al, ). However, a high performance (≥80%) does not entirely prevent faulty Miranda reasoning.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…On average, they evidenced only 2.11 (SD = .90) Miranda misconceptions. Comparatively, this percentage of high performers is slightly higher than found with college undergraduates in general (i.e., 48.7%; see Rogers et al, ). However, a high performance (≥80%) does not entirely prevent faulty Miranda reasoning.…”
Section: Discussionmentioning
confidence: 66%
“…Recognizing the need for more systematic appraisals of Miranda misconceptions, Rogers and his colleagues (Rogers et al, ) developed the Miranda Quiz (MQ).The MQ includes items that address requisite Miranda warning components, general misconceptions about Miranda , and permissible police practices during interrogation that may directly affect Miranda waiver decisions. As summarized by Rogers, Sewell, Drogin and Fiduccia (), the 15 MQ primary items effectively discriminate between defendants with failed versus adequate (a) Miranda vocabulary ( d = 0.93), (b) Miranda comprehension ( d = 0.61), and (c) Miranda reasoning ( d = 0.70).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both laboratory studies and field studies yield similar results: the majority of suspects do not fully understand the warning, and they waive Miranda rights. Research has also demonstrated that innocent suspects are most likely to waive their rights, and those who waive their rights are more likely to confess to crimes they did not commit (Rogers, 2011;Rogers, Hazelwood, Sewell, Harrison, & Shuman, 2008;Rogers et al, 2010). For example, Leo (1996) found that 80% of suspects waived their rights and participated in interrogations without their lawyer present.…”
Section: Overviewmentioning
confidence: 99%
“…Even for healthy adults, comprehension of Miranda warnings and the underlying concepts is hugely variable, 48 and research has shown that individuals with mental illness or intellectual disabilities show poorer understanding of Miranda warnings. Even for healthy adults, comprehension of Miranda warnings and the underlying concepts is hugely variable, 48 and research has shown that individuals with mental illness or intellectual disabilities show poorer understanding of Miranda warnings.…”
mentioning
confidence: 99%